2010
DOI: 10.3892/or_00000921
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mechanism of action for the cytotoxicity elicited by the combination of epigallocatechin gallate and raloxifene in MDA-MB-231 cells

Abstract: Abstract. The anticancer effects elicited by epigallocatechin gallate (EGCG) are well established in various models of cancer, while raloxifene is as an established selective estrogen receptor modulator (SERM), which is not yet clinically utilized for the treatment of breast cancer. Previous study from this laboratory has demonstrated that the combination of EGCG (25 μM) and raloxifene (4 μM) elicits a strong cytotoxic response in MDA-MB-231 human breast cancer cells, which lack the estrogen receptor (ER) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The above changes in protein phosphorylation were associated with a reduced nuclear localization of p63. Thus, the authors concluded that the mechanisms of synergistic interaction of green tea catechins with raloxifene were ER independent [11]. …”
Section: Resultsmentioning
confidence: 99%
“…The above changes in protein phosphorylation were associated with a reduced nuclear localization of p63. Thus, the authors concluded that the mechanisms of synergistic interaction of green tea catechins with raloxifene were ER independent [11]. …”
Section: Resultsmentioning
confidence: 99%
“…The combinatory treatment of EGCG and raloxifene (selective estrogen receptor modulator) reduced p65, a major subunit of NF-κB that was associated with reduced phosphorylation of the AKT, mTOR, EGFR, and S6K, and increased the phosphorylation of stress-activated protein kinases in MDA-MB-231 BC cells [ 168 ].…”
Section: Flavonoids As Suppressors Of Cancer Cell Plasticity and Cons...mentioning
confidence: 99%
“…Triple negative breast cancer (TNBC) is an aggressive and invasive subtype of breast cancer that accounts for 10-20% of all breast cancers [6]. Chemotherapy based on anthracyclines, such as doxorubicin, and taxanes are the main treatment options for patients with TNBC.…”
Section: Introductionmentioning
confidence: 99%